Analisis Hubungan Shift Kerja dengan Stres Kerja pada Perawat di Rumah Sakit Semen Padang Hospital Tahun 2025 - Astrina Aulia; Sonia Fitri Muliana; Miftahurrahmi Fitri; Fluorina Oryza Muslim; Silvia Nengcy; Marhadi Efendi (Universitas Pahlawan Tuanku Tambusai, 2026)
In healthcare settings, nurses play a crucial role as frontline providers in delivering patient care. However, this responsibility often results in high job demands, contributing to both physical and psychological burdens. This study employed a quantitative approach with an analytical observational design using a cross-sectional method. The study variables included demographic factors (age, length of service, and marital status) as independent variables, work shift as the main independent variable, and work stress as the dependent variable. The sample consisted of 69 nurses at Semen Padang Hospital (SPH), selected using a total sampling technique. The results showed a significant relationship between work shift and work stress (p-value = 0.012). Work shift can be considered one of the factors influencing work stress, indicating that appropriate shift arrangements may reduce the risk of work-related stress. It is recommended that hospital management optimize shift work arrangements through workload redistribution, particularly during morning and afternoon shifts, implementation of fair shift rotations, and provision of adequate rest periods. In addition, simplifying administrative tasks, enhancing organizational support, and implementing stress management programs are necessary to reduce nurses’ work stress levels.